A "Triple Threat" to Research Protocols and Logistics: Adolescents, Sexual Health, and Poverty. (January 2016) - Morrison-Beedy, Dianne; Passmore, Denise; Baker, Elizabeth
The purpose of this article is to discuss lessons learned from conducting research with urban communities. A brief overview of the Health Improvement Project for Teens (HIPTeens) will be provided. It will be followed by several suggestions concerning recruitment and retention of participants, challenges related to working in impoverished environments, hiring and training of research teams, interacting with administration and community, and strategies for doing research in diverse settings.